Continuous infusion of ketamine in hypovolemic dogs anesthetized with desflurane - Duque, MJC; Souza, A. P.; Nunes, N.; Honsho, C. S.; Talieri, I. C. (Wiley-Blackwell, 2005)
Objective: To evaluate the cardiorespiratory effects of continuous infusion of ketamine in hypovolemic dogs anesthetized with desflurane.Design: A prospective experimental study.Animals: Twelve mixed breed dogs allocated into 2 groups: saline (n=6) and ketamine (n=6).Interventions: After obtaining baseline measurements (time [T] 0) in awake dogs, hypovolemia was induced by the removal of 40 mL of blood/kg over 30 minutes. Anesthesia was induced and maintained with desflurane (1.5 minimal alveolar concentration) and 30 minutes later (T75) a continuous intravenous (IV) infusion of saline or ketamine (100 mu g/kg/min) was initiated. Cardiorespiratory evaluations were obtained 15 minutes after hemorrhage (T45), 30 minutes after desflurane anesthesia, and immediately before initiating the infusion (T75), and 5 (T80), 15 (T90), 30 (T105) and 45 (T120) minutes after beginning the infusion.Measurements and main results: Hypovolemia (T45) reduced the arterial blood pressures (systolic arterial pressure, diastolic arterial pressure [DAP] and mean arterial pressure [MAP]), cardiac (CI) and systolic (SI) indexes, and mean pulmonary arterial pressure (PAP) in both groups. After 30 minutes of desflurane anesthesia (T75), an additional decrease of MAP in both groups was observed, heart rate was higher than T0 at T75, T80, T90 and T105 in saline-treated dogs only, and the CI was higher in the ketamine group than in the saline group at T75. Five minutes after starting the infusion (T80), respiratory rate (RR) was lower and the end-tidal CO(2) (ETCO(2)) was higher compared with values at T45 in ketamine-treated dogs. Mean values of ETCO(2) were higher in ketamine than in saline dogs between T75 and T120. The systemic vascular resistance index (SVRI) was decreased between T80 and T120 in ketamine when compared with T45.Conclusions: Continuous IV infusion of ketamine in hypovolemic dogs anesthetized with desflurane induced an increase in ETCO(2), but other cardiorespiratory alterations did not differ from those observed when the same concentration of desflurane was used as the sole anesthetic agent. However, this study did not evaluate the effectiveness of ketamine infusion in reducing desflurane dose requirements in hypovolemic dogs or the cardiorespiratory effects of ketamine-desflurane balanced anesthesia.
Keywords: balanced anesthesia; dogs; hemodynamic; hemorrhage